The perception of Iziko South African National Gallery - Visser, Georgina S (The IIE, 2017)
Brand democratisation is a growing trend worldwide as technology is increasing engagement and dialogue between brands and their stakeholders. Brand co-creation, open source branding and democratic brands are increasingly challenging hierarchy and total brand control, affording stakeholders a sense of brand-co ownership. The paper assumes that public brands should be democratic, and that the Iziko national gallery may not yet be perceived as democratic by scholars. In alignment with this study's qualitative nature, a focus group of six representative South African BA branding and art scholars studying in Cape Town between the ages 19-26 years will be carried out and a semiotic analysis of 4 gallery signs will be conducted by participants. These signs include the facade of the gallery, the logo, the intended route through the gallery and the behaviour of gallery goers. This paper found that three of the four signs selected were perceived as predominantly democratic by participants as they embodied a sense of stakeholder agency and opinion. Despite this finding, participants also identified multiple signs that were undemocratic as they embodied a sense of authoritarian power. These were found to be problematic as they played a large role in hindering stakeholder engagement with the brand. In light of the above, this paper hopes to provide insight into the necessary democratic status of the Iziko gallery brand by highlighting which signs maximise a sense of stakeholder engagement
Keywords: Democracy; Brand Democratisation; Brands; Branding; Brand Identity